Characterization and Phylogenetic Analysis of the Mitochondrial Genome Sequence of Nisia fuliginosa (Hemiptera: Fulgoroidea: Meenoplidae). Issue 4 (30th July 2021) - Lv, Sha-Sha; Zhang, Yu-Jie; Gong, Nian; Chen, Xiang-Sheng
Abstract: We explored characterization of the mitochondrial genome (mitogenome or mtGenome) and phylogenetic analysis between 32 Fulgoroid species by sequencing and analyzing the mitogenome of Nisia fuliginosa Yang and Hu, 1985 (Hemiptera: Fulgoroidea: Meenoplidae), thereby making it the first determined mitogenome from the family Meenoplidae. The mitogenome was found to be 15, 754 bp in length and contained 13 protein-coding genes (PCGs), 22 tRNA genes, two ribosomal RNA genes (rRNAs), and a control region. All PCGs started with typical ATN codons, except for nad1, which used GTG as the start codon. Canonical TAA termination codons were found in 10 PCGs and the remaining three genes ( cox2, nad6, and nad1 ) had incomplete stop codons T. All tRNAs could fold into typical cloverleaf secondary structures, with the exception of trnC, trnV, and trnS1 . Additionally, we compared the AT and GC skews of 13 PCGs of 32 Fulgoroidea mitogenomes, on the L-strand, the AT and GC skews were negative and positive, respectively. However, on the H-strand, the AT skew could be positive or negative and the GC skew was always negative. Phylogenetic results showed that the eight families of Fulgoroidea were divided into two large groups. Delphacidae formed a monophyletic group sister to a clade comprising Meenoplidae and other six families (Fulgoridae, Ricaniidae, Flatidae, Issidae, Caliscelidae, and Achilidae). Meenoplidae was located near the clade of Delphacidae, and Fulgoridae was located near the clade of Meenoplidae. Furthermore, Caliscelidae, Issidae, Ricaniidae, and Flatidae are closely related and they collectively formed a sister group to Achilidae.